Evaluasi Usability dan Perbaikan Antarmuka Pengguna Aplikasi Bima Plus Menggunakan Metode Usability Testing dan User-Centered Design (UCD) - Sabilatunnajah Sabilatunnajah; Satrio Hadi Wijoyo; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Bima Plus is a Tri provider application that provides services to support the needs of Tri card users. Based on studies of user reviews on the Google Play Store and interviews with application users, there are usability problems in the Bima Plus application that are felt by users, such as bad user interface, annoying ad headers, slow application performance, and so on. Therefore it is necessary to evaluate usability to be used as a reference in designing the improved user interface of the Bima Plus application. Improvements are made with the User-Centered Design (UCD) approach which places specific users as the main focus in each development process, while the method used in evaluating usability is usability testing. Testing was carried out on five respondents who will work on task scenarios to measure the level of effectiveness and efficiency, as well as interviews to find problems in the application. After that, the respondents filled out the System Usability Scale (SUS) questionnaire to get the level of satisfaction. In the initial evaluation, 22 problems were found which will be improved into low-fidelity prototype and will be evaluated as the first iteration. Improvements are made in the form of high-fidelity which is the final design of the solution design. The results of the evaluation of the final design as second iteration show that the usability level increases by 10% for effectiveness aspects, 23,08% for efficiency aspect, and 31.5 for satisfaction aspects.